ADOLESCENTS, BODY AND PHYSICAL ACTIVITY (Fiep Bulletin - online, 2014)
The body and respective body shapes were always one of society's concerns, more specifically of teenagers. We have tried to investigate, starting from the delimitation of a research field and specific individuals, what are the body representations teenagers present regarding their own bodies. The methodology was designed according to the qualitative research paradigm, having as a reference the case study. The analysis and interpretation of information were constructed from Theme Units which emerged, mainly, from the semi-structured interviews performed with teenagers, from records and notes resulting of observations comprised in field diaries and from theoretical reference on the aspects which constitute the research problem. The questions raised from the construction of those Theme Units have allowed to understand how fundamental body has become to the life of teenagers, since, thinking about it and concerned with its shapes, they use sports practices from the school context as a resource to construct a body representation.
Keywords: adolescent; body; activity physics